IMPLEMENTASI BATAS USIA MINIMAL PERKAWINAN SESUAI UU NOMOR 16 TAHUN 2019 TENTANG PERUBAHAN ATAS UU NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN DALAM PERSPEKTIF HUKUM ISLAM - Tsamratus Syifa' Kafrawi; Lomba Sultan; Hadi Daeng Mapuna (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2022)
The main problem in the research is how to implement of the marriage age limit in Law No. 16 of 2019 at the KUA, Bontoala District, Makassar City. The type of this research are qualitative descriptive research and field research, with data collection techniques through observation, interviews, and documentation, with data analysis techniques through data processing, data presentation and drawing conclusions. The results of this study indicate that the implementation of the revision of the Marriage Law concerning the minimum age of marriage still requires various fulfillments, the KUA of Bontoala District conducts socialization such as lectures and cooperates with the local sub-district. Regarding the addition of the minimum age limit for marriage, it is considered still not effective because it does not have a significant impact and still requires in-depth evaluation in preventing underage marriages in Bontoala District. Keywords: Marriage Age, Marriage Regulation, Islamic Law.